2011
DOI: 10.1016/s1701-2163(16)34983-0
|View full text |Cite
|
Sign up to set email alerts
|

Using Clinical Symptoms to Predict Adverse Maternal and Perinatal Outcomes in Women With Preeclampsia: Data From the PIERS (Pre-eclampsia Integrated Estimate of RiSk) Study

Abstract: Maternal symptoms of preeclampsia are not independently valid predictors of maternal adverse outcome. Caution should be used when making clinical decisions on the basis of symptoms alone in the preeclamptic patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…The sensitivity and specificity of the symptoms in predicting adverse maternal outcomes were, respectively, as follows: Yen et al in an analysis of the PIERS data reported that of 2023 women who underwent assessment, 52 % experienced at least one preeclampsia symptom, with 5.2 and 5.3 %, respectively, experiencing an adverse maternal or perinatal outcome. No single symptom was found to be a good predictor of adverse perinatal outcomes [10].…”
Section: Discussionmentioning
confidence: 94%
“…The sensitivity and specificity of the symptoms in predicting adverse maternal outcomes were, respectively, as follows: Yen et al in an analysis of the PIERS data reported that of 2023 women who underwent assessment, 52 % experienced at least one preeclampsia symptom, with 5.2 and 5.3 %, respectively, experiencing an adverse maternal or perinatal outcome. No single symptom was found to be a good predictor of adverse perinatal outcomes [10].…”
Section: Discussionmentioning
confidence: 94%
“…Despite advances in the understanding of PE, diagnosing this condition still relies on clinical findings (i.e., hypertension and proteinuria) that are poor markers of disease severity [31] . Indeed, there are cases of normotensive PE or PE without proteinuria in which the pathophysiology and risks are similar to those of classic PE [9] .…”
Section: Characterization Of Atypical Preeclampsiamentioning
confidence: 99%
“…Specifically, the CLIP intervention consists of:

Community engagement including women from the communities, dyadic household decision-makers (husbands, fathers-in-law) and community leaders about: pre-eclampsia, its origins, symptoms, signs and potential consequences, pre-permissions for maternal transport and fundraising activities for transport and treatment costs;

Provision of HDP-oriented antenatal care through household visits by community healthcare providers (cHCPs) who carry a mobile health (m-health) application for identifying women at risk of pre-eclampsia. The m-health application is programmed with a validated Pre-eclampsia Integrated Estimate of Risk (PIERS) on the Move (POM) [9, 10];

Use of the CLIP package for women with a CLIP ‘trigger’ (i.e. oral antihypertensive therapy or intramuscular (i.m.)
…”
Section: Introductionmentioning
confidence: 99%
“…The m-health application is programmed with a validated Pre-eclampsia Integrated Estimate of Risk (PIERS) on the Move (POM) [9, 10];…”
Section: Introductionmentioning
confidence: 99%